Analisis Yuridis Kewenangan Pemerintah Desa Dalam Pengelolaan Dana Desa Untuk Kesehatan Di Kabupaten Banyumas - Alan Bayu Aji; Kartika Dwi Chandra Sari (Fakultas Hukum Universitas Islam Indonesia, 2021)
This research departs from the use of village funds which are still oriented towards infrastructure development in the midst of the low Human Development Index in Banyumas Regency which is influenced by the level of community health. The purpose of the research is to identify first, the authority of the Village Government in the use of village funds for health sector activities according to applicable regulations. Second, the role of the Village Government in utilizing village funds for health sector activities in Banyumas Regency. Third, the Village Fund utilization model for future public health activities. The research method used is normative juridical with statutory, case and conceptual approaches. The results of the study show that first, the authority of the village government for the utilization of village funds in the health sector is regulated in the Minister of Village Regulation Number 01 of 2015. Second, it was found that the role played by the village government in 50 villages in Banyumas is still lacking, it is proven that only 6% allocation of village funds for health. Third, the model that will be built in the future is the use of a bottom-up system in village development planning, health census, formation of peer education as well as socialization and periodic monitoring from the government.